Combined Aortic Valve Replacement and Renal Cell Carcinoma Thrombectomy. (March 2017) - Martinelli, Susan M.; Lobonc, Andrew; Wallen, Eric M.; Stansfield, William E.; Selph, J. Patrick; Calvo, Benjamin; Kumar, Priya A.
Although nephrectomy for renal cell carcinoma with inferior vena cava invasion is a common procedure, it is rare to have level IV invasion necessitating cardiopulmonary bypass (CPB). Furthermore, it is exceptionally rare to perform cardiac surgery concomitantly with this resection. We report a case in which an aortic valve replacement was done in the same surgical setting as a level IV thrombectomy. We have demonstrated that although it can be difficult to manage the coagulopathy post-CPB, this can be successfully accomplished with adequate prior preparation and a coordinated team effort.